Market participation of smallholder common bean producers in Malawi - Lifeyo, Yanjanani (International Food Policy Research Institute, 2017)
This study has analyzed the factors affecting common bean production and marketing decisions by agricultural households in Malawi. The empirical results from applying the triple hurdle model to the IHS3 data demonstrate that different sets of factors affect smallholder farmers’ production, market participation and the intensity of participation decisions with respect to common beans. The location of the farmer, ownership of a radio, receipt of production extension services and FISP benefits, distance to main road and distance to the nearest market affected the agricultural household’s decision to produce common beans.